Contribution of Defective PS Recognition and Efferocytosis to Chronic Inflammation and Autoimmunity - Kimani, Stanley Gititu; Geng, Ke; Kasikara, Canan; Kumar, Sushil; Sriram, Ganapathy; Wu, Yi; Birge, Raymond B. (Frontiers in Immunology, 2014)
The rapid and efficient clearance of apoptotic cells results in the elimination of auto-antigens and provides a strong anti-inflammatory and immunosuppressive signal to prevent autoimmunity. While professional and non-professional phagocytes utilize a wide array of surface receptors to recognize apoptotic cells, the recognition of phosphatidylserine (PS) on apoptotic cells by PS receptors on phagocytes is the emblematic signal for efferocytosis in metazoans. PS-dependent efferocytosis is associated with the production of anti-inflammatory factors such as IL-10 and TGF-β that function, in part, to maintain tolerance to auto-antigens. In contrast, when apoptotic cells fail to be recognized and processed for degradation, auto-antigens persist, such as self-nucleic acids, which can trigger immune activation leading to autoantibody production and autoimmunity. Despite the fact that genetic mouse models clearly demonstrate that loss of PS receptors can lead to age-dependent auto-immune diseases reminiscent of systemic lupus erythematosus (SLE), the link between PS and defective clearance in chronic inflammation and human autoimmunity is not well delineated. In this perspective, we review emerging questions developing in the field that may be of relevance to SLE and human autoimmunity.